Sleep disturbances in late pregnancy: associations with induction of labor - Lähde, Henna; Karlsson, Hasse; Karlsson, Linnea; Perasto, Laura; Varis, Viliina; Rinne, Kirsi; Paavonen, E. Juulia; Polo-Kantola, Päivi (Springer Nature, 2025)
Purpose
Sleep disturbances, which are common during pregnancy, may compromise labor. Nevertheless, little is known about associations between sleep disturbances and the likelihood of ending up induction of labor (IOL). Accordingly, we aimed to evaluate the connections between sleep disturbances during pregnancy and IOL.
Methods
Altogether 1778 women from the FinnBrain Birth Cohort Study with gestation weeks over 37 + 6 were enrolled in the study. The women were divided into IOL (n = 331) and spontaneous onset of labor (SOL, n = 1447) groups. Sleep disturbances in late pregnancy were evaluated using the Basic Nordic Sleep Questionnaire. Logistic regression analyses were conducted with adjustments for age, body mass index, parity, smoking, and depressive symptoms.
Results
Sleep disturbances were frequent in both IOL and SOL groups. In the IOL group 43.0% and in the SOL group 39.0% had poor general sleep quality (P = 0.186). Nocturnal awakenings occurred most commonly, in 94.0% and 93.9%, respectively (P = 0.653). In the IOL group, more women (22.7%) were habitual snorers than in the SOL group (17.0%, P = 0.017), however, the difference lost the statistical significance in adjusted analysis (P = 0.848). Women in the IOL group were more likely to be short sleepers (< 7 h) compared to those in the SOL group (20.2% and 15.4%, respectively, P = 0.034) with no difference after adjustment (P = 0.133). The two groups showed no differences in sleep loss (P = 0.252).
Conclusions
Deterioration in sleep quality was noticeable in pregnant women, but it was unconnected with IOL. As the frequency of IOL is increasing, more research for related risk factors is needed.